Optimal Dynamic Capital Budgeting - Malenko, Andrey (Review of Economic Studies, 2019)
Abstract I study optimal design of a dynamic capital allocation process in an organization in which the division manager with empire-building preferences privately observes the arrival and properties of investment projects, and headquarters can audit projects at a cost. Under certain conditions, a budgeting mechanism with threshold separation of financing is optimal. Headquarters: (1) allocate a spending account to the manager and replenish it over time; (2) set a threshold, such that projects below it are financed from the account, while projects above are financed fully by headquarters upon an audit. Further analysis studies when co-financing of projects is optimal and how the size of the account depends on past performance of projects.